2004
DOI: 10.1167/iovs.04-0151
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Pax6 Expression Disturbs Lens Fiber Cell Differentiation

Abstract: The data demonstrate that high levels of Pax6 expression disrupt normal fiber cell differentiation and maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 56 publications
3
54
2
Order By: Relevance
“…Mutation of these factors causes cataracts in both mouse models and humans (Glaser et al, 1994;Hanson et al, 1994;Semina et al, 1998;Wigle et al, 1999;Blixt et al, 2000;Brownell et al, 2000;Duncan et al 2000;Ring et al, 2000;Semina et al, 2000Semina et al, , 2001Jamieson et al, 2002;Lyon et al, 2003;Berry et al, 2004;Duncan et al, 2004;Rajaram and Kerpolla, 2004). Most of these transcription factors are downstream of Pax6 in the lens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation of these factors causes cataracts in both mouse models and humans (Glaser et al, 1994;Hanson et al, 1994;Semina et al, 1998;Wigle et al, 1999;Blixt et al, 2000;Brownell et al, 2000;Duncan et al 2000;Ring et al, 2000;Semina et al, 2000Semina et al, , 2001Jamieson et al, 2002;Lyon et al, 2003;Berry et al, 2004;Duncan et al, 2004;Rajaram and Kerpolla, 2004). Most of these transcription factors are downstream of Pax6 in the lens.…”
Section: Resultsmentioning
confidence: 99%
“…Pax6 is upstream of Sox2 (Furuta and Hogan, 1998), Pax6 and Sox2 cooperatively regulate gene expression (Kamachi et al 2001, Aota et al, 2003, and Sox2 is required for the maintenance of Pax6 (Donner et al, in press). Appropriate temporal, spatial, and quantitative control of Pax6 expression is required for appropriate lens morphogenesis (Hill et al, 1991;Glaser et al, 1994;Hanson et al, 1994;Grindley et al, 1995;Quinn et al, 1996;Schedl et al, 1996;Brown et al, 1998;Ashery-Padan et al, 2000;Duncan et al, 2000;van Raamsdonk and Tilgham, 2000;Dimanlig et al, 2001;Duncan et al, 2004). PAX6 mutation is causative for several congenital eye defects in humans including aniridia, Peters' anomaly and cataract (reviewed in Prosser and van Heyningen, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…GAD65, EGAD, and GABA were initially detected in the lens placode, which is the site of expression of multiple transcription factors known as regulators of lens induction and fiber cell differentiation, such as Pax6, Six3, Eya, Dach1, Mafs, Sox2, Sox3, and Prox1 (Kawauchi et al, 1999;Kim et al, 1999;Wigle et al, 1999;Ogino and Yasuda, 2000;Ring et al, 2000;Duncan et al, 2002Duncan et al, , 2004Cui et al, 2004;Purcell et al, 2005). Pax6, Sox, c-Maf, and Prox1 have consensus binding sites in conserved regions of GAD65 and GAD67 genes (F. Erdélyi and Z.D.…”
Section: Transcriptional Regulation Of Gad In the Lens: Involvement Omentioning
confidence: 99%
“…Normal development of the inner retina is directly influenced by a well-elaborated spatial and temporal pattern of PAX6 expression. 1,[6][7][8][9][19][20][21] However, little is known about PAX6 expression and function in the adult mammalian retina. De Melo et al 22 showed that several homeobox genes including Pax6 are expressed in the young adult mouse retina and we recently reported continuous expression of PAX6 in the young, adult, and old normal human retina.…”
Section: Pax6 Expression and Retinal Cell Death In A Transgenicmentioning
confidence: 99%